Image-Guided Robotic Radiosurgery for the Treatment of Same Site Spinal Metastasis Recurrences - Ehret, Felix; Mose, Lucas; Kufeld, Markus; Fürweger, Christoph; Windisch, Paul; Haidenberger, Alfred; Schichor, Christian; Tonn, Jörg-Christian; Muacevic, Alexander (Frontiers in Oncology, 2021)
Background Due to recent medical advancements, patients suffering from metastatic spinal disease have a prolonged life expectancy than several decades ago and some will eventually experience relapses. Data for the retreatment of spinal metastasis recurrences occurring at the very same macroscopic spot as the initially treated lesion are limited. Previous studies mainly included recurrences in the boundary areas as well as other macroscopic parts of the initially affected vertebrae. This study exclusively analyzes the efficacy and safety of spinal reirradiation for recurrences on the same site utilizing single-session robotic radiosurgery. Materials and Methods Patients between 2005 and 2020 who received radiotherapy for a spinal metastasis suffering from a local recurrence were eligible for analysis. Only patients undergoing a single-session reirradiation were included. All recurrences must have been occurred in the same location as the initial lesion. This was defined as a macroscopic recurrence on computed tomography (CT) occurring at the same site as the initial spinal metastasis. All other lesions, including those in the boundary areas or other parts of the initially affected vertebrae were excluded. Results Fifty-three patients with fifty-three lesions were retreated for spinal metastases. The median dose and number of fractions for the initial radiotherapy were 36 Gy and 15, respectively. Eleven patients were initially treated with stereotactic body radiotherapy. Retreatment was performed with a median dose of 18 Gy prescribed to a median isodose of 70%. The crude local control was 77% after a median follow-up of 22.2 months. Patients experiencing a second recurrence received a lower dose (p = 0.04), mostly below 18 Gy, and had a worse coverage (p = 0.01) than those showing local tumor control. 51% of patients experienced an improvement in pain control after treatment delivery. Besides, four vertebral compression fractures (7% of patients) but no further adverse events higher than grade 2 were observed. Conclusion Single-session robotic radiosurgery appears to be a safe, time-saving, and effective treatment modality for spinal metastasis recurrences occurring in the same initial location if a considerable dose and coverage can be applied. Treatment results are comparable to reirradiated metastases in the boundary areas.